Firms' rationales for CEO duality: Evidence from a mandatory disclosure regulation - Marc Goergen; Peter Limbach; Meik Scholz-Daneshgari (University of Cologne, Centre for Financial Research (CFR), 2019)
Exploiting the 2009 amendments to Regulation S-K, we provide unique evidence on the first-time disclosure of the reasons firms state for combining (separating) the roles of CEO and chairman. The stated reasons support both agency theory and organization theory. They are more numerous and comprise more words, including more positive words, for firms with duality. Examining the announcement returns to firms' disclosures, we find that investors evaluate the most frequently cited reasons for CEO duality by considering the firm's characteristics.
Keywords: G14; G34; G38; 330; CEO Duality; Board of Directors; Corporate Governance; Regulation S-K; Textual Analysis